SsNEP2 Plays a Role in the Interaction Between Sclerotinia sclerotiorum and Coniothyrium minitans - Huizhang Zhao; Zihang Zhu; Yueli Xu; Haixuan Wang; Jiatao Xie; Jiasen Cheng; Daohong Jiang; Yanping Fu (Journal of Fungi, 2025)
Sclerotinia sclerotiorum, a fungal pathogen that is spread worldwide and causes serious diseases on crops, can be parasitized specifically by the mycoparasite Coniothyrium minitans. SsNEP2, encoding a necrosis-inducing protein in S. sclerotiorum, was previously inferred to play a role in the virulence to host plants. In this study, silencing of SsNEP2 in S. sclerotiorum had no significant (p < 0.01) influence on mycelial morphology, while overexpression led to lower mycelial growth and more branches. When amended with the fermentation broth of the SsNEP2 silencing mutants, conidial germination of C. minitans was promoted, while conidial production decreased. When parasitized by C. minitans, enhanced resistance of the SsNEP2 silencing mutants and weaker resistance of the overexpressed transformants were observed compared to the wild-type S. sclerotiorum strain 1980. In addition, the expression of SsNEP2 in C. minitans enhanced mycelial parasitism on S. sclerotiorum and restored the effect of silencing SsNEP2 in S. sclerotiorum on mycoparasitism. Thus, we highlight the role of SsNEP2 as a PAMP-like protein in the mycoparasitism between C. minitans and its host fungus S. sclerotiorum. SsNEP2 can be used to promote the biological potential of C. minitans.